A Molecular Web: Endoplasmic Reticulum Stress, Inflammation, and Oxidative Stress - Chaudhari, Namrata; Talwar, Priti; Parimisetty, Avinash; Lefebvre d’Hellencourt, Christian; Ravanan, Palaniyandi (Frontiers in Cellular Neuroscience, 2014)
Execution of fundamental cellular functions demands regulated protein folding homeostasis. Endoplasmic reticulum (ER) is an active organelle existing to implement this function by folding and modifying secretory and membrane proteins. Loss of protein folding homeostasis is central to various diseases and budding evidences suggest ER stress as being a major contributor in the development or pathology of a diseased state besides other cellular stresses. The trigger for diseases may be diverse but, inflammation and/or ER stress may be basic mechanisms increasing the severity or complicating the condition of the disease. Chronic ER stress and activation of the unfolded protein response (UPR) through endogenous or exogenous insults may result in impaired calcium and redox homeostasis, oxidative stress via protein overload thereby also influencing vital mitochondrial functions. Calcium released from the ER augments the production of mitochondrial Reactive Oxygen Species (ROS). Toxic accumulation of ROS within ER and mitochondria disturb fundamental organelle functions. Sustained ER stress is known to potentially elicit inflammatory responses via UPR pathways. Additionally, ROS generated through inflammation or mitochondrial dysfunction could accelerate ER malfunction. Dysfunctional UPR pathways has been associated with a wide range of diseases including several neurodegenerative diseases, stroke, metabolic disorders, cancer, inflammatory disease, diabetes mellitus, cardiovascular disease and others. In this review we have discussed the UPR signaling pathways, and networking between ER stress induced inflammatory pathways, oxidative stress and mitochondrial signaling events which further induce or exacerbate ER stress.